Criminal Justice Drug Abuse Treatment Studies (CJDATS): Detention to Community (DTC), 2006-2008 (United States) - Liddle, Howard A. ([Verlag nicht ermittelbar], 2011)
The Detention to Community (DTC) study addresses several priority areas of the CJDATS collaborative. First, the study will adapt existing science-based interventions in order to develop specialized services that will address drug abuse, delinquency, and sexual risk-taking among juveniles detained in detention facilities. Second, the study proposes to test an innovative, phasic, multiple-systems intervention in which the in-detention work provides a platform for the adolescent's return to the community. This bridge is created by linking the in-detention and outpatient treatment components in ways that reflect the consensus in the literature regarding the need for integrative, comprehensive interventions for criminal justice involved, substance abusing individuals (Cook, 1992; Altschuler and Armstrong, 1999). The interventions meld public health and public safety concerns, and target members in multiple systems influential to a teen's developmental outcomes, including the adolescent's family and school, the judiciary, and treatment providers. Thus, they go beyond the fragmented, sometimes competitive treatment models too often seen in standard criminal justice and drug treatment settings (Belenko, 2000). Third, consistent with recommendations from the literature, NIDA has designated HIV/AIDS prevention in juvenile justice facilities as an urgent public health priority (NIDA, 2002). This study would test a family-based HIV/AIDS prevention intervention in comparison to standard HIV prevention. Finally, the systems-change possibilities and public policy implications of the proposed study are high, because the study would examine processes and outcomes of implementing the intervention in the real world settings in which the findings are meant to apply -- juvenile detention centers and outpatient community-based drug treatment agencies that work with young offenders (Armstrong and Altschuler, 1998).